2012
DOI: 10.1074/jbc.m112.349902
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Up-regulated FoxO1 Expression in Follicular Granulosa Cell Apoptosis Induced by Oxidative Stress

Abstract: Background: Granulosa cell (GC) apoptosis is the main cause of follicular atresia, and oxidative stress is involved in this process. Results: GC apoptosis is caused by FoxO1 activity in oxidative stress. Conclusion: FoxO1 is critical in oxidative stress-induced GC apoptosis. Significance: Our results detail the mechanism of follicular atresia and indicate that FoxO1 is a potential target in preventing follicular atresia from oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(167 citation statements)
references
References 80 publications
7
157
3
Order By: Relevance
“…15 Moreover, a previous study showed that ip injection of 3-NP elevated ovarian ROS levels in mice. 10 In ovarian GCs collected from 3-NP mice in the present study, a significant increase in caspase 3, Bim, and PUMA mRNA related to increased oxidative stress was found compared to controls (Figure 2A). These results confirm that 3-NP induces ovarian oxidative stress in mice and activates apoptotic pathways in follicular GCs.…”
Section: Administration Of 3-np Induced Gc Apoptosis and Upregulated supporting
confidence: 53%
“…15 Moreover, a previous study showed that ip injection of 3-NP elevated ovarian ROS levels in mice. 10 In ovarian GCs collected from 3-NP mice in the present study, a significant increase in caspase 3, Bim, and PUMA mRNA related to increased oxidative stress was found compared to controls (Figure 2A). These results confirm that 3-NP induces ovarian oxidative stress in mice and activates apoptotic pathways in follicular GCs.…”
Section: Administration Of 3-np Induced Gc Apoptosis and Upregulated supporting
confidence: 53%
“…Animals were injected intraperitoneally with 12.5 mg/kg 3-NPA twice daily for 7 consecutive days at 12-h intervals (8 a.m. and 8 p.m.). The dose of 3-NPA used in the study was based on doses used in literature published from our laboratory (Shen et al, 2012). PC was dissolved in normal saline and supplemented to the animals by intragastric administration twice daily at a dose of 100 mg/kg body weight because this was reported to be the most effective dose (Bagchi et al, 1998a;Sato et al, 1999).…”
Section: Experimental Design and Treatmentmentioning
confidence: 99%
“…3-NPA, a natural toxin produced by various plants and fungi, is an inhibitor of succinate dehydrogenase and induces oxidative stress of mitochondrial origin (Fontaine et al, 2000;Kim et al, 2000). ROS levels that were specifically increased in follicular granulosa cells, but not other tissues, were detected following intraperitoneal injection of mice with 3-NPA (Shen et al, 2012). 3-NPA can significantly increase the production of lipid peroxides and oxidized protein levels both in the mitochondria and in the cytosol (Fu et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 Previous studies have clearly demonstrated that granulosa cell (GC) apoptosis is the cellular mechanism responsible for follicular atresia in mammals 4 and that DNA fragmentation, caspase activation, up-regulation of pro-apoptotic and downregulation of anti-apoptotic gene expression are involved in this process. 5 In mammals, GC apoptosis is regulated by multiple factors such as reactive oxygen species (ROS), hormones, BCL2 family members and growth factors and cytokines, including tumor necrosis factor (TNF)-a and interleukin-6. 6 However, the precise molecular mechanism still needs to be further illuminated.…”
Section: Introductionmentioning
confidence: 99%